Peran Manajemen Efikasi Diri Siswi Dalam Pembentukan Budaya Bahasa Arab di Sekolah (Studi Kasus Di SMP Tashfia Putri Boardinh Kota Bekasi, Jawa Barat) - Harleli; Akhmad Sunhaji; Ahmad Zain Sarnoto (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2025)
This study focuses on the role of self-efficacy management among students in the formation of an Arabic language culture at SMP Tashfia Boardinh School. In both school and dormitory language practices, students' motivation, abilities, and participation in Arabic practice have not been optimal. The majority of Grade VII (71%) and Grade VIII (57%) students were recorded violating the rules for using the designated language. This is due to limited interaction in Arabic conversations among students and between students and mentors, as well as insufficient supervision in the dormitory. The management of students' self-efficacy was assessed based on two main informants. Informant 1 (KI 1) showed progress in self-efficacy management, although there remains a gap between the set goals and actual achievements, particularly in understanding Quranic vocabulary and using Arabic in daily conversations. This underachievement affected KI 1's self-confidence and motivation. However, with positive emotional management and support from teachers, KI 1 was able to reduce the stress experienced. Informant 2 (KI 2), on the other hand, demonstrated good self-efficacy management across all aspects, including goal-setting, self-reflection, and stress management. Overall, both informants met the criteria for self-efficacy management in the formation of Arabic language culture, although KI 1 requires a more structured approach. This research employed a qualitative approach through in-depth interviews, participatory observations, and document analysis involving various stakeholders, including students, teachers, and other relevant parties.